Financialization against Industrialization: a regulationnist approach of the Brazilian Paradox - Eliane Araújo; Miguel Bruno; Débora Pimentel (Revue de la Régulation)
The process of trade and financial liberalization has fundamental consequences on the development of Brazilian industry. The relatively rapid reconfiguration of the institutional form of insertion into the international regime, in a context of intensification of foreign competition and lack of consistent industrial policy has been the engine of significant changes in the structure of industry. At the end of the 1990s, a new mode of regulation emerged, based on a new accumulation regime as result of the structural changes observed. Several empirical studies have highlighted the occurrence of deindustrialization and Dutch disease caused by the strong appreciation and volatility of the exchange rate, while others, on the contrary, see the opportunity for modernization of plants from the lower prices of imported capital goods. This paper provides new empirical evidence on the chances of industrialization and Dutch disease, which marks the current debate on the effects of real exchange rate appreciation to the Brazilian economy. For its relevancy regarding the future of the industry in this country, our work also examines the recent evolution of the Brazilian growth in the context of the spread of the North-American crisis. This regime has been characterized by a strong dominance of financial accumulation ; it constraints on investment and consumption decisions, which would explains the sharp drop of the industrial production in late 2008, when the global financial markets were largely affected. Consequently, the prospects of Brazil’s macroeconomic performance depend crucially on the reactions of the current mode of regulation, and the regime of accumulation, to the challenges posed by the current stage of evolution of the global economy. By using the concept of financialization it is possible to achieve a better understanding of the relationship between industrial structure changes and financial liberalization.